Ischaemic Necrosis of Pinnae in a Dachshund Dog – A Report - Nath, Krishna; Unny, N Madhavan; Pillai, Usha Narayan (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
Ischaemic necrosis or thrombo-vascular necrosis of pinnae or pinnal margin vasculopathy is a slowly progressive idiopathic syndrome characterized by wedge-shaped devitalization and necrosis of the distal pinnae. It may occur either in unilateral or bilateral forms, bilateral affection being more common. Initially, an erythematous swelling and discoloration may be noted in the center of the medial aspect towards the apex of pinnae. Later, a necrotic ulcer may be seen in the center of the lesion, progressing to exudation and hemorrhage. In chronic cases, the areas of ulceration undergo complete necrosis resulting in deformity. Although there is no age, sex, and breed predisposition, certain breeds like Dachshunds and Chihuahuas are commonly affected (Morris et al., 2013; Nuttall et al., 2005). This communication reports a case of ischaemic necrosis of pinnae in a Dachshund dog with its successful clinical management.